Udje Družbe sv. Mohorja v videmski nadškofiji do leta 1900 - Vovko, Andrej (Traditiones (Ljubljana), 1999)
Družba sv. Mohorja, a publishing company which supported national awareness, education and cultural progress among Slovenes in the basis of Christian principles, was equally active among the Slovenes living in Slavia Veneta and Resia in the Udine archdiocese. Based on the roster of St. Mohor's Association (Družba sv. Mohorja) listed in the association's calendars in the author gives a complete survey of all its members in the Udine archdiocese prior to 1900
Keywords: založbe; založništvo; Družba sv. Mohorja; Hermagoras Society; Videm; nadškofija; kulturna zgodovina; Italija; Italy; zgodovinski prikazi